Rancang Bangun Media Pembelajaran Avionic - Radio Theory II Berbasis Multimedia Animasi pada ATKP Medan - Dwiyanto Dwiyanto; Catra Indra; Ahmad Faisal; Iswandi Idris; Rizaldy Khair (STMIK Budi Darma, 2020)
The importance of Learning Media is used by ATKP Medan to continuously improve the quality of learning. The problem that is often encountered in avionic learning is the limited resources available because to access avionic learning the cadets must access from the CBT LAB and cannot be from elsewhere. This is because Avionic software is only installed inside the lab and cannot be learned from outside the lab. The purpose of this research is to improve the digital avionic-Radio Theory II learning process which is packaged in multimedia animation to make it easier for cadets to learn avionic Radio Theory II without having to access it in the laboratory. The method used in this research is to use the MDLC Multimedia Development Life Cycle method, namely the Concept concept, design, material collection, assembly, testing, distribution, distribution, The resulting output is an animated video product and publication to the ISSN journal